Religious experience: methodological aspects of research - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article contains classical and post-classical psychoanalysis, in terms of the methodology of religious studies. The understanding of religion in psychoanalytic theory as a religious experience is emphasis. The religious experience is one of the main concepts in the methodological provisions of psychoanalysis. Religious experience is regarded as the result of human mental activity, but not such that belongs to the sphere of transcendental; it is as a human need; like human`s protection from the problems of the world, as an opportunity to achieve; as the possibility to inner harmony.